(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
The present paper presents descriptions of 10 bryozoan species from material deposited at the Geological Centrum Göttingen, Germany. The studied material comes from the Lower Devonian rocks (Konĕprusy Limestone, Pragian), exposed in a quarry near Zlatý Kůň in Central Bohemia. Described bryozoans comprise 8 trepostome and 2 cryptostome (rhabdomesine) species. One genus and species is new: the cryptostome (rhabdomesine) Paracuneatopora striata gen. n., n. sp., and 7 species are new: trepostomes Leioclema elegans n. sp., Atactotoechus divulgatus n. sp., Loxophragma fistulosum n. sp., Leptotrypella punctata n. sp., Microcampylus obscurus n. sp., Dyscritella bohemica n. sp., and the rhabdomesine Orthopora tenuis n. sp. Furthermore, two trepostomes Monotrypa bohemica Prantl, 1933 and Anomalotoechus cf. typicus Duncan, 1939 were identified in this material. The described fauna displays palaeozoogeographic relations to the Lower Devonian (Pragian) of Morocco and the Middle Devonian of Michigan (USA).